The Performance of Common Stocks in Relation to Their B/M and P/E ratios: An Empirical Study of Value Investing in UK Market - Liu, Tianqi (2012)
Nowadays value investing has been applied all around the world. Numerous studies have been done on evaluating the performance of typical value investing indicators such as cash flow-to-book ratio, sale growth, B/M ratio and P/E ratio and dividend yield. However, seldom studies focus on their performance in UK stock market. This paper employs two basic metrics of value investing strategy, which are firms’ book-to-market ratio and price-to-earnings ratio. The testing period covered a total number of 14 years’ return from April 1998 to April 2012. Both monthly average return and annual mean compound return for value stocks and growth stocks are computed, and compared with the market average return.